The effects of strain rate and grain size on nanocrystalline materials: A theoretical prediction. (15th December 2015) - Jiang, Bingyun; Zhang, Shaorui
Abstract: The article describes a dislocation-based model for the coupling effects of strain rate and grain size on the mechanical behavior of nanocrystalline materials. Two important experimental findings about nanocrystalline materials are explained by the model: 1. the difference of the dependencies of strain rate sensitivity (SRS) on grain size between FCC and BCC nanocrystalline materials and 2. the abnormal dependency of activation volume on thermally activated stress. Our analysis shows that the strain rate-dependent behavior of nanocrystalline materials is mainly determined by the ratio between the activation volumes in grain and grain boundary regions. Graphical abstract: Highlights: The coupling effects of strain rate and grain size on nanocrystals are analyzed. We determine the key factor for strain rate-dependent behaviors of nanocrystals. We predict the different strain rate sensitivity of FCC and BCC nanocrystals. We explain the dependence of activation volume on thermally activated stress. Theoretical predictions agree well to experimental findings.